Leverage, profitability, corporate governance mecanism and earning management: cases in manufacturing company in Indonesia Stock Exchange - Prawida, Novria; Sutrisno, Sutrisno (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
Earnings management is a form of manager manipulation in company external financial report in aim for individual profit. This research aim to analyze leverage efek, profitability, the amount of commissioner board and audit committee towards earnings management in bank that registered in BEI 2016-2017. This research is quantitative research and the sample conducted with purposive sampling method. This research apply secondary resource data from annual financial report of registered bank in BEI 2016-2017. There are 32 bank that fulfill criteria that researcher submit. This research apply multiple linier regression analysis method using IBM SPSS program. The results shows that leverage (DAR) has positive significant effect towards earnings management, profitability (ROA) doesn’t have significant effect towards earnings management, amount of commissioner board (BS) and audit committee (KA) doesn’t have significant effect toward earnings management.